I've seen the promised land : the life of Dr. Martin Luther King, Jr. - Myers, Walter Dean, 1937-2014 (HarperCollinsPublishers, 2004)
Pictures and easy-to-read text introduce the life of civil rights leader Dr. Martin Luther King, Jr.